KEWAJIBAN PAJAK SUBJEKTIF DAN OBJEKTIF UNTUK MENENTUKAN KEWAJIBAN MEMILIKI NPWP - Lusy Suprajadi (Bina Ekonomi, 2009)
Anyone who has fulfilled conditions both subjective and objective according to income tax law must have  tax identification  number (NPWP). Tax identification number is a number issued to taxpayers by the tax office  to identify  taxpayers and to assist them  in fulfilling  their tax obligations. Conversely, NPWP should withdraw when  tax payers  do not comply with conditions under  income tax law. This paper describes  how to determine someone, corporation,  or non-profit organization  should commence or end  in performing  tax obligations.